1976
DOI: 10.1093/clinchem/22.5.663
|View full text |Cite
|
Sign up to set email alerts
|

Technical pitfalls in measurement of venous plasma NH3 concentration.

Abstract: Measurement of venous plasma NH3 in normal subjects by the ion-exchange method of Forman [Clin. Chem. 10, 497 (1964)] in a hospital clinical laboratory gave a mean value of 640 mug/liter (range, 300-1320 mug/liter; intraassay, intra-individual, and inter-individual coefficients of variation, 8, 47, and 47%, respectively). The following conditions adversely affect the reproducibility of the test: pollution of laboratory atmosphere and glassware by NH3-containing detergents; smoking by patient or analyst; delay,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…It is thus impossible to send samples to a specialized laboratory by mail. [42][43][44][45][46] Although several authors mention this problem as the main reason for avoiding the use of AMM tests, this disadvantage has been largely resolved by the introduction of the Blood Ammonia Checker II. e This analyzer proved to be a simple, reliable, and relatively inexpensive alternative to the standard automated enzymatic assay.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus impossible to send samples to a specialized laboratory by mail. [42][43][44][45][46] Although several authors mention this problem as the main reason for avoiding the use of AMM tests, this disadvantage has been largely resolved by the introduction of the Blood Ammonia Checker II. e This analyzer proved to be a simple, reliable, and relatively inexpensive alternative to the standard automated enzymatic assay.…”
Section: Discussionmentioning
confidence: 99%
“…A nontraumatic, non-probing venipuncture was required for an acceptable specimen for this study. 3 In addition to the blood collected for the physician-ordered tests, two 3mL evacuated lithium heparin tubes (BD Vacutainer®) were collected from each individual and labeled with pre-printed study number labels. Immediately after labeling, one of the extra tubes was placed in the side pocket of a 5"x9" biohazard bag filled with approximately one cup of ice, and the second extra tube was maintained at room temperature (23°C) in a 5"x9" biohazard bag.…”
Section: This Study Was Approved By Virginia Commonwealth University'mentioning
confidence: 99%
“…1 Numerous studies have shown that plasma ammonia levels increase in vitro over time and may be falsely elevated if the specimen is not chilled "on-ice" prior to processing and analysis. [1][2][3][4][5][6][7] The sources of the increase in plasma ammonia concentration in vitro reportedly include deamination reactions in erythrocytes and platelets, and the deamidation of plasma glutamine by γglutamyltransferase (γ-GT). 4,6,[8][9][10] While these studies demonstrated the clinical importance of plasma ammonia specimen integrity, many of these studies were performed with blood collection techniques and analytical methods that are no longer in use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with liver disease, one cigarette smoked 1 hour before venipuncture was reported to increase fasting blood ammonia levels by 10 umol/L. 20 It is obvious that ammonia determinations have to be performed in a laboratory environment free of open urine samples or open bottles containing high ammonia standards. Ong et al 13 used an enzymatic method whereas Nicolao et al 14 used the Blood Ammonia-Checker II (BAC-II; Menarini, Florence, Italy) for ammonia measurement.…”
Section: Commentsmentioning
confidence: 99%